Polymorphisms in SLC44A1 are associated with cognitive improvement in children diagnosed with fetal alcohol spectrum disorder: an exploratory study of oral choline supplementation. Issue 2 (19th April 2021) - Smith, Susan M; Virdee, Manjot S; Eckerle, Judith K; Sandness, Kristin E; Georgieff, Michael K; Boys, Christopher J; Zeisel, Steven H; Wozniak, Jeffrey R
ABSTRACT: Background: The essential nutrient choline provides one-carbon units for metabolite synthesis and epigenetic regulation in tissues including brain. Dietary choline intake is often inadequate, and higher intakes are associated with improved cognitive function. Objective: Choline supplements confer cognitive improvement for those diagnosed with fetal alcohol spectrum disorder (FASD), a common set of neurodevelopmental impairments; however, the effect sizes have been modest. In this retrospective analysis, we report that genetic polymorphisms affecting choline utilization are associated with cognitive improvement following choline intervention. Methods: Fifty-two children from the upper midwestern United States and diagnosed with FASD, ages 2–5 y, were randomly assigned to receive choline (500 mg/d; n  = 26) or placebo ( n  = 26) for 9 mo, and were genotyped for 384 choline-related single nucleotide polymorphisms (SNPs). Memory and cognition were assessed at enrollment, study terminus, and at 4-y follow-up for a subset. Results: When stratified by intervention (choline vs. placebo), 14–16 SNPs within the cellular choline transporter gene solute carrier family 44 member 1 ( SLC44A1 ) were significantly associated with performance in an elicited imitation sequential memory task, wherein the effect alleles were associated with the greatest pre-/postintervention improvement. Of these, rs3199966 is a structural variant (S644A) and rs2771040 is a single-nucleotide variant within the 3′ untranslated region of the plasma membrane isoform. An additive genetic model best explained the genotype associations. Lesser associations were observed for cognitive outcome and polymorphisms in flavin monooxygenase-3 ( FMO3 ), methylenetetrahydrofolate dehydrogenase-1 ( MTHFD1 ), fatty acid desaturase-2 ( FADS2 ), and adiponectin receptor 1 ( ADIPOR1 ). Conclusions: These SLC44A1 variants were previously associated with greater vulnerability to choline deficiency. Our data potentially support the use of choline supplements to improve cognitive function in individuals diagnosed with FASD who carry these effect alleles. Although these findings require replication in both retrospective and prospective confirmatory trials, they emphasize the need to incorporate similar genetic analyses of choline-related polymorphisms in other FASD-choline trials, and to test for similar associations within the general FASD population. This trial was registered at www.clinicaltrials.gov as NCT01149538.